Fenologia, sistemas de tutoramento e produção de Physalis peruviana na região de Pelotas, RS. - Lima, Cláudia Simone Madruga (2009)
The great development of successful non-traditional crops for the production and area planted, shows that Brazil, as a producer is discovered and entering into new and interesting markets. A small fruit with big potential is Physalis peruviana, because its short cycle, possibility of high economic returns, coupled with nutritional properties. However, little is known of their development, growth and management, especially for conditions edafoclimáticas de Pelotas / RS. In this work, the main objective was to the phenological behavior of Physalis peruviana and adapt management techniques for the conditions of the southern edafoclimáticas RS. The study was conducted in Pelotas, Brazil in the period 2007 to 2008. For the first phase of the experiment was performed in three sowing seasons. In the second phase of the experiment were performed transplant seedlings in two to four times associated systems staking of plants, "V" inverted, triangular, with vertical and vertical bamboo with fitilho. For the first phase of the experiment were determined the dates of occurrence, days after emergence and degree-days for the following phenological phases: true leaves, the first branch, floral budding, formation of basal shoots, fruit trees, the leaves start to fall, and harvest. Also identified were the following phenological stages: swollen flowers and open flowers. Fortnightly from the transplant were evaluated for length, diameter and number of leaves of the main stem, number of shoots, number of flowers and fruits. Were also conducted monthly assessments of the quality of the fruit, as the fruit and total mass, skin color of fruit, total soluble solids (SST), titratable acidity (AT), SST / AT. For the second stage variables answers were: increase the length and diameter of the main stem, the section area of stem, fresh weight of shoot and root, estimated productivity, production efficiency, rate of harvest, the fruit weight, color skin of fruit, total soluble solids (SST), titratable acidity (AT), SST / AT and total carotenoids. In the first phase, the most representative results were verified in the first sowing date. For the second phase, it was shown that the first season of transplantation associated with the system of staking "V" and inverted triangular provided agronomic behavior appropriate for the plants and fruits of Physalis. It is the cultivation of Physalis in the region of Pelotas, Brazil. September is the recommended time of sowing, and staking systems "V" and inverted triangles are the most appropriate in the management of Physalis plants. (Support: CAPES)